Strategic human resource management: A framework from an Islamic perspective - Ishak, Mohd. Shuhaimi (2013)
An effective human resource management is crucial for every organization’s success. The main purpose of human resource management is to ensure that an organization achieves the optimal level of benefits from its employees while at the same time giving them the material and psychological rewards for their accomplishment. In view of the ever-changing environments at the workplace due to the changes in the industry, technology, policy and competition, human resource management becomes a strategic and comprehensive approach in managing people. The paper attempts to shed light on the salient features of Islamic framework in the strategic human resource management. Against this background, the paper endeavors to highlight the capabilities and strengths of the framework which enables the employees to contribute effectively and productively to the overall direction of the organization in meeting its goals and objectives. This paper concludes that Islam is not only a religion but also is a way of life.